THE INFLUENCE OF FLY ASH AND FOSROC CEBEX-100 ON THE MECHANICAL PROPERTIES OF STABILISED SOFT SOIL - Farah Salsabila Rahma; Yerry Kahaditu Firmansyah; Himatul Farichah (Jurnal Pensil)
The problem of soft soil in infrastructure, specifically in road construction, will cause ongoing issues due to the nature of soft soil, which often undergoes shrinkage and swelling, potentially leading to failure in the structures above it. The solution of stabilizing the soil using chemical methods while also utilizing waste that is harmful to the environment has become very common, such as the use of fly ash material. This research focuses on the stabilization of soft soil using two stabilizing materials, namely fly ash and fosoc cebex-100, to improve the strength of problematic soil so that it can support the load of the construction above it. Fly ash was added  at 20%, 25%, and 30% of soil weight, and Cebex-100 at 0,45% of fly ash weight. The sample variations were subjected to physical tests, including Unconfined Compression Tests and shear strength tests, to determine the changes in physical and mechanical properties that occurred after the addition of the additives. The research results obtained from the unconfined compressive strength and elastic modulus parameters showed an improvement as the fly ash composition increased. The soil shear strength test identified 25% fly ash as the optimum variation, resulting in a cohesion value of 34.49 kN/m² and a friction angle of 7.66°. It can be concluded that the addition of fly ash and cebex-100 to problematic soil conditions can improve the physical and mechanical properties of the soil.